Activity Based Management For Increase Cost Efficiency and Profitability PG Krebet – East Java - Fatimah, Annisa; Nadhifah, Fincavenia Hafidhatun (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this research is to identify production activities and analyze the improvement of cost efficiency and profitability through the implementation of Activity Based Management. The data used were primary and secondary data data through interviews and documentation data collection techniques. This research method was descriptive qualitative method. The results showed that there were found four non-value-added activities and the selection of alternatives continuous improvements was cost reductions in each non-value-added activity, cost efficiency produced by sugar and drip products by 0.52%, which was valued at Rp. 762,596,166. The implementation of ABM by managing production costs can be applied US a continuous improvement step to production activities. Keywords: Activity Based Management (ABM), Activity Based Costing (A B C), Cost efficiency, Profitability